Forest vegetaion conditions and vegetation of fir forest of west tien-shan (Experimental biology, 2015)
The article contain forest vegetation conditions that are conventionally divide by the temperature regime and thedegree of hydration for the three West Tien-Shan fir forests zones with significantly differing from each other relevant tothem climatic characteristics. The current state and a brief description of the vegetation are given.
Keywords: Semenov’s fir tree; fir forests; endemic; flora; tree; bushes; herb